Additional dates of Sir Andrew Smith’s Illustrations of the Zoology of South Africa - Low, Martyn E. Y.; Evenhuis, Neal L. (Zootaxa, 2014)
We update the collation of the dates of publication of Smith’s Illustrations of the Zoology of South Africa provided by Waterhouse (1880) and Barnard (1950, 1952). In the case of nine parts, we are able to provide more accurate dates of publication (including day-dates for seven of these parts). For workers of invertebrate taxonomy, we provide an accurate date of publication for W. S. Macleay’s volume on Annulosa.